Detecting and measuring Microplastic pollution in Al Hoceima City's harbor, northern Morocco - Iliass Achoukhi; Yahya EL Hammoudani; Khadija Haboubi; Abdelhak Bourjila; Abdelaziz Touzani; Kamal Reklaoui; Fouad Dimane (Case Studies in Chemical and Environmental Engineering)
This study investigates microplastic pollution in Al Hoceima City's harbor, Northern Morocco, with a focus on their isolation, identification, and quantification. In December 2023, surface water and sediment samples were systematically collected using manta nets and core samplers. The samples underwent wet sieving, drying, and digestion using hydrogen peroxide with an iron catalyst to remove organic matter. Density separation with a saturated sodium chloride solution was employed to isolate microplastics, which were then analyzed using ATR-FTIR spectroscopy for polymer identification. The analysis revealed a dominance of polyethylene (70.2 %) and polypropylene (20.5 %) among the microplastics, primarily in fiber, fragment, and film forms, with sizes ranging from 0.10 to 6 mm. Predominant size categories were 0.2–0.5 mm, accounting for over 50 % of the total, and clear and blue were the most common colors. The average microplastic density was calculated at 9.40 ± 4.50 items/m³. This study highlights the widespread distribution of microplastics in the harbor, identifying their sources and impacts, while providing a robust methodology and findings to inform future marine pollution mitigation efforts in the Mediterranean region.